The cash-for-care reform and immigrant fertility: Fewer babies of poorer families? - Lars Dommermuth; Adrian Farner Rogne; Astri Syse (Statistics Norway, Research Department, 2022)
Cash-for care policies are contested in many contexts, as they represent an incentive for childrearing over work that may reduce labour market participation, especially among immigrant women. From 1 July 2017, immigrants (both the mother and the father) from outside the European Economic Area must have at least 5 years of residence in Norway to be entitled to cash-for-care benefits. Previous research indicates that this reform did not lead to increased labour market participation of mothers and fathers treated by the reform. In this article, we examine whether the changes in the cash-forcare benefits policy have resulted in a substantive change in income and if the reform had an impact on the childbearing behaviour among those affected by the reform. Our descriptive analyses indicate no change in employment rates and household income. To detect possible changes in fertility, we employ a Difference-in-Difference approach, in which we compare the treatment group with four comparison groups. Overall, we find no substantial effect of the cash-for-care reform on childbearing behaviour.
Keywords: J13; J6; J15; 330; fertility; cash-for-care; immigrant fertility